The Role of Serum Level of Indoleamine 2,3–dioxygenase 1 (IDO1) in Patients with Prostate Cancer (Medico Legal Update, 2021)
Prostate cancer or carcinoma of prostate is the development of cancer in the prostate a gland in the malereproductive system. This is a cross sectional, hospital based study. This study was carried out at theOncology Center in Kirkuk City- Iraq from the 1st of February 2020 to the end of June 2020. A verbalconsent was taken from each Men included in this study whether considered as a case or control. Sixty_ Seven men with prostatic cancer were screened to participate in the present study. Men with prostaticcancer attended to Oncology Center were enrolled in this study. The diagnosis of prostate cancer was madeby the patient’s file contain information about his state after take agreement from each Men included inthis study, that is mean that the diagnosis of prostate cancer was according to discussion of the oncologist. Men ages were between 52 to 89 years, and they were from the center and periphery of Kirkuk City.Forty-Seven Men with prostatic cancer were considered as a study group, three Men did not meeting theinclusion criteria and 17 Men refuse to participate in this study due to the personal reasons. Forty apparentlyhealthy Men without prostatic cancer and with negative family history. Each Men with benign tumor, benignprostatic hyperplasia or prostatitis diseases were excluded from this study. By using a sterile disposablesyringe, 5 ml of venous blood sample was drawn from the vein of each Men at morning and was kept intodisposable gel tube and allowed to clot for(2hour) at room temperature, then each sample was centrifugedat 6000 rpm for 10 minutes to obtain serum. The serum was aspirated by mechanical micropipette andtransferred into clean Eppendorf tubes which labeled with number, then put this Eppendorf tubes in urinecups for safety and addition more information like name, date, number and stored at - 20 0C until the timeof estimation. Serum of the patients and controls had assay for: Human IDO1 (Indoleamine 2,3-dioxygenase1) and Human acid phosphatase/prostate by ELISA. The study demonstrated that, the rate of prostate canceroccurrence was increased with age and majority of patients were belonged to the age group (70-79 years).The study also showed non-significant difference between patients and control regarding their BMI mean(27.36±5.16 vs. 27.24±3.34kg\m²) respectively. The study showed that, serum level of IDO1 enzyme waselevated significantly (P